PENGARUH MODEL INKUIRI TERBIMBING DENGAN BANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA PEMBELAJARAN IPS - Rosita Rosita; Fitri Fitri; Rini Setyowati (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This study aims to see the effectiveness of using the guided inquiry model with audio-visual assistance on cognitive learning outcomes of social studies class IV of elementary school on the theme of my hero and to find out how much influence the guided inquiry model with the assistance of audio-visual media has on cognitive learning outcomes. The research uses a quantitative approach, quasi-experimental design method, and non-equivalent control group design. The population of this study was 11 elementary schools in North Singkawang District, whose accreditation was B. The experiment was carried out on samples that were selected at simple random. The selected sample is SDN 82 Singkawang. The data collection instrument in the form of essay questions is used to measure knowledge (cognitive) abilities. Of the 10 questions, the results of the validity test were 8 questions having moderate validity and 2 questions having very high validity with a reliability level of 0.752. Data were tested and analyzed using the t-test and effect size. The results of data processing show that: (1) There are differences in social studies learning outcomes of experimental and comparison class students with t-test> ttable, namely 4.717 > 2,01 ; (2) The model in the experimental class has a high effect on cognitive learning outcomes in student social studies learning 1.65 (high criterion). So it can be concluded that the audio-visual assisted guided inquiry model is effective in increasing cognitive learning outcomes in social studies learning for fourth-grade elementary school students